Creating long-term high performing teams - Lancaster, S.; Burke, V. (Routledge handbook of elite performance sport, 2019)
Introduction: In order to truly understand how to build long-term high performing teams it is important to change our mindset on how we 'view' a team. A strong team has a strong 'team spirit' and that spirit can grow or diminish in its size depending on many factors, a lot of which are in the leader's control. In this chapter I would like to try and describe what are the essential components in building a long-term high performing team that has a strong 'team spirit' and ultimately a chance of reaching its full potential. Using the Performance Pyramid (see Figure 37.1) the starting point is for the leader to assess in each of the layers on the Pyramid (Culture, Identity, Higher Purpose, Behaviours and Standards, Ownership, and Player Led Leadership) and this will then guide their decision-making on where to focus their attention on building or enhancing the team that they are working in. Where you score your team 's effectiveness will directly affect the proportion of time that will need to be spent on the different dimensions of the Performance Pyramid. The key here is always to Start at the bottom and ensure the foundations are strong with a good culture. Your judgement on where to focus your attention as the leader depends on your know ledge of the Organisation and your entry point in to it. For example, if you came through the Organisation from within you may already have a good insight into the culture and environment, where the team sits in relation to its maturity or wether it needs renewing. Having coached England Saxons team from 2007-11, I was able to observe the England senior team 's evolution during that period, so when I came in as head coach, I felt I had a good insight into what needed to be done, how it needed to be done, and at what level to Start building a long-term high-level performing team. We focused on getting the culture right, selecting the right people, and making sure we were all aligned to a cause. From there we worked on building trust and building relationships, moving on to identity in the second year: what it means to play for England, the identity of England. Then we continued to work our way through the pyramid. Conversely when I arrived at Leinster I had no real know ledge of the Organisation, so I did my homework beforehand in order to find out as much historical information as possible about the team. My first month there was spent asking good questions about the environment, while observing and learning about it, and making an assessment about where I saw strengths and where things needed to improve. Culturally I felt that Leinster was strong; there were some areas that needed adjustment, and the players needed a vision - in this case centring on the European Cup, which was achieved this year. Once I understood that Leinster's identity was very strong, I was able to move on to behaviours and Standards, and then to continue working through the pyramid to the very top where the players ultimately drive the programme. The pyramid is useful here because its layers can help you to formulate the right questions to ask. Find out as much as you can and how much the players are involved in driving all of this.